TM1-6 Intramedullary spinal cord tumours – a single centre 10 year retrospective review. Issue 3 (14th February 2019) - Richards, O; Goacher, E; Derham, C
Abstract : Objectives: To identify clinically relevant predictors of progression free survival by retrospectively analysing the anatomical location, pre- and post-operative function and histology in intramedullary spinal cord tumours from a single neurosurgical centre over 10 years. Design: Retrospective review. Methods: 49 patients were identified from a surgical database. Variables collected included pre-and post-operative Frankel Grade and Modified McCormick Scale assessments, tumour histology, extent of resection and length of follow up. Chi-Squared, Kaplan-Mier Survival and Mann-Whitney U-Tests were completed. Results: There was a statistically significant relationship between identification of the tumour plane and extent of resection (p<0.01), along with the extent of resection and recurrence (p<0.01). Compared to the other histological subtypes, ependymoma's demonstrated a significantly greater extent of resection (p=0.02). There was a significant relationship between the grade of tumour and progression free survival (p<0.01). We did not find a significant relationship between pre- and post-operative neurological function and survival. Conclusions: Tumour plane and the extent of tumour resection are significant determinants of progression free survival. Ependymoma, whilst being the commonest histology in our series were also the most resectable. Whilst complete resection reduces the rate of recurrence, tumour grade is the most important predictor of outcome.